Humor dalam Suasana Ramadan - M Hermintoyo (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The existence of social media makes it easy for people to communicate and express themselves and so on. so there is an urge to express or inform something not only information but provide entertainment in the form of humor. In certain situations certain themes will emerge, for example during the month of Ramadan there will be humor themes related to events or activities related to Ramadan such as, when starving, breaking fast, sahur, forgiveness-forgiveness, holiday allowances, etc. . Humor is done in order to wait for the maghrib drum to be delivered so that there is activity during the fasting. In general, communicating humor gives each other humor that mobile phone users have. Creative journals used are usually play words that mean ambiguous.